2018
DOI: 10.1001/jamanetworkopen.2018.5805
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Physicians Excluded From US Medicare and State Public Insurance Programs for Fraud, Health Crimes, or Unlawful Prescribing of Controlled Substances

Abstract: Key Points Question What were the characteristics of physicians who have been excluded from US Medicare and state public insurance programs? Findings In this cross-sectional study assessing all physician exclusions from 2007 to 2017, the number of physician exclusions grew by 20% per year (equivalent to 48 additional exclusions per year) to encompass approximately 0.3% of US physicians in 2017. Exclusions were more common in the West and Southeast census re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 19 publications
6
13
0
Order By: Relevance
“…Similar to previous research findings, low-risk specialties (mostly primary care physicians) were generally more likely than high-risk (largely secondary care physicians) to be excluded by the OIG (see Chen et al, 2018;Pande & Maas, 2013;Pontell et al, 1985). Low-risk medical specialties were largely overrepresented while high-risk specialties were generally underrepresented among physicians placed on the list.…”
Section: Risk Of Medical Malpractice Payment By Medical Specialtysupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to previous research findings, low-risk specialties (mostly primary care physicians) were generally more likely than high-risk (largely secondary care physicians) to be excluded by the OIG (see Chen et al, 2018;Pande & Maas, 2013;Pontell et al, 1985). Low-risk medical specialties were largely overrepresented while high-risk specialties were generally underrepresented among physicians placed on the list.…”
Section: Risk Of Medical Malpractice Payment By Medical Specialtysupporting
confidence: 80%
“…Similar to past research studies, female physicians were less likely than male physicians to be excluded by the OIG (see Chen et al, 2018;Pande & Maas, 2013). Females were underrepresented and males were overrepresented amongst physicians who were placed on the LEIE.…”
Section: Sexsupporting
confidence: 72%
“…This finding coincides with the findings of the 2018 study by Chen et al, which found that physicians who were excluded from Medicare and state public programs due to fraud were commonly male physicians. 5 Moreover, a retrospective, cohort study of 2251 malpractice claims reported to the Ophthalmic Mutual Insurance Company from 1990 to 2008 found that men were sued 54% more often than females over the period studied, indicating a prevalence of claims against men in not only medical fraud, as observed in this study, but also medical malpractice. 10…”
Section: Discussionsupporting
confidence: 56%
“…Chen et al previously examined the characteristics of physicians from all specialties who were excluded from US Medicare and state public programs for fraud, health crimes, or unlawful prescribing of controlled substances. 5 Excluded physicians tended to be older, male, and/or osteopathic physicians. The most common specialties were family medicine, psychiatry, internal medicine, anesthesiology, surgery, and obstetrics/gynecology.…”
Section: Introductionmentioning
confidence: 99%
“…Patients need to bear the time and health cost of repeated discharge and hospitalization, resulting in poor medical experience and low PBBMI. Some scholars believe that these unreasonable medical behaviors are related to the lack of the BMIS regulatory system and regulatory tools ( 65 ). Although Harbin has followed national policies regarding supervision measures such as legislation, multi department coordination, social integrity system construction, and information construction in recent years, these methods are still in the preliminary exploration stage and need to be gradually improved.…”
Section: Discussionmentioning
confidence: 99%